Comportamento do consumidor de produtos orgânicos: uma análise na perspectiva da teoria da cadeia de meios e fins - Vilas Boas, Luiz Henrique (2005)
Accompanying the transformations evident in the world food market, changes in consumer purchase behavior have been observed in several food sections, with a tendency in growth for organic products, which can be seen as one of the great food tendencies of the last decade. The objective of this thesis was to investigate, through the Means Ends Chain Theory, consumer behavior of organic food products in open markets in the city of Belo Horizonte, MG, with reference to the identification and characteristics of the products and the relationships between them and also the relationship between the consequences of purchase and consumption in relation to the consumers' grades, structure presupposed by this theory. In sight of this, a literature revision was made with relationship to the evolution of the organic market, concepts of market strategies and consumer behavior, and the consumer's of organic foods behavior. For theoretical sustenance, a structure based on the evolution of marketing research in perspective of values in the study of the consumer's behavior, the Means Ends Chain Theory was used. A laddering technique was used for research, allowing through the representation of the information in the head office of joined relationships and, later, in the hierarchical value map, to identify orientations of the consumers' perception. The great number of attributes, consequences and identified values, revealed a complex structure that characterizes these consumers' cognitive perspectives. The occurrence of perceptible and nonperceptible attributes of the product served as means of unveiling purchase attitude, verifying growing perspective of attributes non-perceptible. The attributes " non-toxic" and "better flavor" were identified as predominant in the conformation of the dominant chains. The experience with relationship to the use of the product and communication, resulting in credibility with relationship to the organic product and the purchase process, are considered decisive elements in this market. The orientation perceptions were decisive for guaranteeing the constitution of the product and also the health and safety of the consumer. Based on these orientation perceptions seven large specific groups that characterized the consumers' of chemical free vegetables cognitive perspectives and organic vegetables were identified: "Practical - it makes my life easier", "social Conviviality", "Socially and environmentally responsible", "Health and economy", "safe eating", "Pleasure and nostalgia" and "Pleasure and energy." With relationship to the values, as many domains of individual interest stimulation as collective interests were evidenced, and identified in three large groups: the first one formed by representative values of domains of individual interest stimulation ("to Live life well", "life Quality" and "Longevity") representing more than half of all the identified relationships between attributes and values; a second one formed by intermediate values, that showed as many domains of individual interest stimulation as collective ("Harmony-balance" and "Peacefulness"); and a third formed by representative values of domains of collective interest stimulation ("Socialize" and "Happiness"). It can be concluded that there occurred a prevalence of relationships with characteristics of domains of individual interest stimulation and that the values "to live life well" and "Harmony-balance" are the values whose relationships with the attributes showed more representatives.